Breaking hearts and taking names: A case of sarcoidosis related effusive-constrictive pericarditis. (March 2020) - Valentin, Ramon; Keeley, Ellen C.; Ataya, Ali; Gomez-Manjarres, Diana; Petersen, John; Arnaoutakis, George J.; Drew, Peter; Barnes, Matt; Patel, Divya C.
Abstract: Introduction: Pericardial involvement of sarcoidosis is a rare cause for acute heart failure, and usually occurs as a result of the development of a pericardial effusion leading to cardiac tamponade. Even rarer still, is the manifestation of constrictive pericarditis. We report a case of sarcoidosis with lung, pleural, and pericardial involvement with effusive-constrictive pericarditis leading to cardiac tamponade. Case presentation: A 34-year-old Caucasian man presented for evaluation of a history of worsening exertional dyspnea, edema, and weight loss. A high-resolution chest computed tomography showed diffuse pulmonary nodules with upper lobe predominance and in a perilymphatic distribution; large right pleural effusion; and large pericardial effusion with pericardial thickening. A transthoracic echocardiogram demonstrated early tamponade physiology for which a pericardial drain was placed. After removal of the drain he developed cardiogenic shock from cardiac tamponade attributed to the reaccumulation of a pericardial effusion and urgent pericardial window was performed. Serial echocardiography was concerning for organization and localization of the pericardial fluid. Cardiac magnetic resonance imaging demonstrated a significant reduction in pericardial slippage between the parietal and visceral layers around the heart collectively suggestive of constrictive pericarditis. Confirmation of effusive-constrictive pericarditis was noted on right heart catheterization. He then underwent pericardiectomy, which on histopathologic evaluation demonstrated non-necrotizing granulomas, thus confirming pericardial involvement of sarcoidosis. Conclusions: We report a case demonstrating unique manifestations of sarcoidosis; effusive-constrictive pericarditis presenting with acute congestive heart failure. Highlights: The most common manifestation of pericardial sarcoidosis is a pericardial effusion. Constrictive pericarditis is a rare presentation of pericardial sarcoidosis and can lead to cardiac tamponade. Clinicians should be aware of the life threatening manifestations of sarcoidosis.